Evaluation of bending property of 3D printed carbon fiber composite - Ali, Hind B. (Edelweiss Applied Science and Technology, 2025)
Optimized printing configurations for additive manufacturing can produce complex geometries in polymers, ceramics, metals, and composites; hence, the process is often simply referred to as 3D printing. Thermoplastic materials, and within them, the most common ones applied through FDM extrusion-based 3D printing, are indeed the thermoplastic composites or the fiber-reinforced ones. It is used in general as it is easy to operate, change materials, cost-effective, and produces long and short fiber-reinforced products. Carbon fiber-reinforced polymer composites are commonly used in several industries due to their enhanced mechanical properties. Specifically, these composites have high specific stiffnesses and tensile strengths. However, access to composite materials in various forms is now limited by the production restrictions associated with different technologies. The primary purpose of carbon fiber-reinforced polymer is to augment the capabilities of polymer-based components. However, several different factors, including the manufacturing method, matrix material, fiber orientation, and length, affect the properties of composite materials. Our objective in this endeavor is to utilize FDM 3D printing to combine thermoplastic and carbon fiber to create a continuous composition of carbon fiber and thermoplastic (CFRC). The composite specimen that is added is submitted to a flexural test that follows the manufacturing process. The test of flexibility revealed delamination. This led to the research, analysis, and exploration of the interface between research. Ultimately, suggestions for additional research, enhancements to research, and recommendations were made.